-2x+2+3x=-5+6x-5x

Simple and best practice solution for -2x+2+3x=-5+6x-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+2+3x=-5+6x-5x equation:



-2x+2+3x=-5+6x-5x
We move all terms to the left:
-2x+2+3x-(-5+6x-5x)=0
We add all the numbers together, and all the variables
-2x+3x-(x-5)+2=0
We add all the numbers together, and all the variables
x-(x-5)+2=0
We get rid of parentheses
x-x+5+2=0
We add all the numbers together, and all the variables
7!=0
There is no solution for this equation

See similar equations:

| (5t-13)+(3t+3)=120 | | w^2+2w+1=2w^2-5w+11 | | -5m+6=3 | | 1/3d-4=28 | | 3(x-2)=-7+0.5 | | 8=y+29/8 | | (9.5+x+4)/4=5.5 | | 168/108=14/x | | -4=-9+9y | | 2z+20–3z=1.5(6z+4) | | 80x+1=54x+27 | | 80x+1=54x+73 | | -5x+3x+3=-5x+3x+3 | | 9r+-17=55 | | (x+30)°=x° | | 3(x-2)=-7(1/2) | | 15.48=3d | | 40m+0.25=25+0.45m | | -3x–4=5 | | 7x+6=2-10 | | 2/5(x–2)=-3 | | p-9=-0.4 | | 60/x-60/2x=3 | | 224=-7(8+5p) | | 5x–7=-67 | | -4|r-7|=-12 | | 12x+1=12x-1 | | 11x-7+15x+5=180 | | 4d-1/3=28 | | (x+5)÷2=10 | | 1/2x5x6=15 | | 134=x+113+x+27 |

Equations solver categories